IN THE NOVELS OF ABDULLA QADIRI - HISTORY (Academicia Globe: Inderscience Research, 2023)
This article is a brief biography of Abdulla Qadiri, a representative of Turkestan revolutionary movement, playwright, novelist, short story writer, and the contribution of his novels to the formation of a historical vision of the socio-economic and political situation of the Kokand khanate in the 19th century (Khudayor Khan’s khanate).